Mediating Role of Employee Readiness to Change in the Relationship of Change Leadership with Employees' Affective Commitment to Change - Cici Anggraini; Muhammad Alfikri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is entitled Pramana Coffee Marketing Communication Strategy in Attracting Consumer Interest. The purpose of this study was to determine Pramana Coffee's marketing communication strategy. The research method used in this research is descriptive qualitative research method and in data collection techniques through library research, Internet searching, observation and interviews with informants who have been selected through observation. The theory used in this research is the Marketing Mix Theory by Kotler & Armstrong. The author draws conclusions from the results of research analysis based on the concept of Marketing Mix Theory by Kotler & Armstrong. That Pramana Coffee has implemented 4 (four) marketing mix elements in carrying out its marketing communication strategy. After doing this research, the thing that the researcher wants to suggest to Pramana Coffee is to be able to add products in the future so that Pramana Coffee can optimize the promotion process so that it can attract more consumers.